SME access to public procurement: An analysis of the experiences of SMEs supplying the publicly funded UK heritage sector. Issue 4 (December 2015) - Loader, Kim; Norton, Sophie
Abstract: Previous research examining the relationship between small suppliers and public sector procurers has tended to portray small and medium enterprises (SMEs) as being homogeneous. However, there have been calls for further study of the SME population, in relation to public procurement, in recognition of its diverse nature. This paper contributes to the debate by exploring the experiences of SMEs supplying traditional building skills to the publicly funded UK heritage sector. Our analysis demonstrates that the heritage sector has distinct characteristics which affect the public procurement of traditional building skills. Specifically, the uncertain nature of the work and the key role of the architect demand a specialist input from the public sector procurer. Other experiences compare with those reported across the broader SME population, including the preference to supply directly rather than subcontract, the reluctance to form consortia and the benefit of demonstrating a track record. We argue that this evidence of distinctiveness within the heritage sector suggests that policymakers and practitioners need a greater understanding of the requirements of SME suppliers in different sectors. Attempts to improve participation and success of SMEs in the public procurement process require that consideration is given to the need for a distinct, sector-driven, remedy. Highlights: Contributes new evidence about SMEs experiences in supplying the UK public sector. The influence of sector is explored in order to consider whether it provides a fruitful area for further study. Our analysis of small traditional building firms supplying the heritage sector provides evidence which legitimises SME sector as an area of investigation. The distinctiveness of the heritage sector creates a sector specific dimension. A conversational interview technique encouraged an open and natural sharing of experiences, in turn producing a rich dataset.